Representation of the linguistic and creative personality of the author in the english-language children’s poetic texts - Pikalova, Anna; Пікалова, Анна (Одеса, 2018)
Cтаття присвячена виявленню основних особливостей мовної особистості автора англомовних дитячих поетичних текстів. Мовну особистість дитячого поета розглядаємо як сукупність здібностей, характеристик, таланту і хисту носія конкретної мови, що обумовлюють створення автором поетичних текстів, призначених для дітей. Мовна особистість дитячого поета вирізняється володінням високорозвиненої мовної компетенції, досконалими знаннями літературної мови, вибором і вживанням мовностилістичних засобів у відповідності до мети, здатністю створювати римовані тексти з чіткою ритмічною організацією, обізнаністю з дитячою психофізіологією. Зазначене обумовлює індивідуально-авторську своєрідність лінгвотворчості. Жодна творчість неможлива без уяви, саме тому творчість характеризують як складний психічний процес, пов'язаний з характером, інтересами, здібностями особистості. Уява дитячого поета постійно працює, творячи для дітей. Дитячий поет створює нові образи, зрозумілі дитячому сприйманню, на основі фонових знань реципієнтів, з орієнтацією на їх емоціосферу. Це складний процес, що свідчить про креативну складову мовної особистості дитячого поета. Мовна гра постає одним із видів лінгвокреативної діяльності. Найтиповішими прикладами мовної гри у текстовому просторі дитячих віршів виявляється звукове обігравання слів (алітерація, звуконаслідування) і повтори, що вербалізуються на різних мовних рівнях. Креативність мовної особистості дитячого поета обумовлена хистом до римування, майстерністю створювати дитячі поезії, що актуалізують мовнокреативний процес, результатом якого являються дитячі поетичні тексти, що творені лінгвокреативною особистістю, яка володіє високим рівнем мовної компетенції. Креативне середовище охоплює дитячу читацьку аудиторію з усіма її особливостями та обумовлене лінгвокультурним контекстом. Cтруктура креативності мовної особистості дитячого поета охоплює мотиваційні, емоційні, інтелектуальні, комунікативні та інші властивості.

This article is devoted to the identification of the main features of the linguistic personality of the author, which are represented in the English-language children's poetic texts. The linguistic personality of the children’s poet is determined as a combination of abilities, characteristics, talent and ability of the author. The linguistic personality of the children’s poet is distinguished by the possession of highly developed linguistic competence, the perfect knowledge of the literary language, selection and use of the linguistic means in accordance with the aim, the ability to create rhymed texts with a clear rhythmic organization, awareness of children’s psychophysiology. It determines the author’s originality of linguistic creative activity. Any creativity is impossible without imagination, which is why creativity is characterized as a complex mental process associated with the peculiarities, inter- ests, abilities of the individual. Imagination of the children's poet is constantly working, creating for children. The children's poet creates new images that are comprehensible to the children's perception, based on the background knowledge of the recipients, with an orientation towards their emotional sphere. The language game is one of the types of linguistic and creative activity. The most typical examples of language game in the text space of children's poems are the sound vocalization (alliteration, onomatopoeia) and repetitions that are verbalized at different language levels. The creativity of the linguistic personality of the children’s poet is due to the rhyming skills, the skill to create children's poetry, which actualize the linguistic and creative process, the result of which are children's poetic texts, created by a linguistic and creative personality who possesses a high level of linguistic competence. The creative environment covers the children's readership with all its peculiarities and is due to the linguistic and cultural context. The structure of the creativity of the linguistic personality of the children's poet covers motivational, emotional, intellectual, communicative, and other peculiarities.
Pikalova, Anna. Representation of the linguistic and creative personality of the author in the english-language children’s poetic texts / A. Pikalova // Одеський лінгвістичний вісник. – 2018. – Вип. 11. – С. 44-52. DOI https://doi.org/10.32837/2312-3192-2018-11-44-52
Keywords: Research Subject Categories::HUMANITIES and RELIGION; Дитячий поет; мовна особистість; мовна компетенція; англомовні дитячі поетичні тексти; уява; креативність; мовна гра; креативна діяльність; Children’s poet; linguistic personality; linguistic competence; the English-language children's poetic texts; imagination; creativity; language game; creative activity